Influence Of Online And Physical Classroom On Students Academic Performance In University Of Ilorin, Nigeria - BABALOLA Ebenezer Omolafe; ONASANYA Samuel Adenubi (Jurnal Pendidikan Ilmu Sosial, 2023)
This study investigated the influence of online and physical classroom on student academic performance. The descriptive research of the survey type was employed to achieve the purpose of this study. The target population for the study consisted of students in five randomly selected faculties in University of Ilorin, Nigeria. Proportionate sampling technique was used to select the sample from each of the selected faculties in the University. Simple random sampling techniques were used to draw 200 students who constituted the actual sample size for the study. The data obtained from the respondents were analyzed using descriptive and inferential statistics. Frequency and mean score was used to answer the research questions. ANOVA was used to test hypothesis one while t-test was used to test hypothesis two. The findings of this study were that: both online and physical learning positively influenced students’ academic performance; students faced challenges while learning both physical and virtually; students engaged online performed better than those engaged physically with the mean different of 2.38; there was a significant difference between the academic performance of students taught in an online classroom based on faculty; and there was no significant difference between the academic performance of students taught in an online class based on gender. It was concluded that physical and online education have many things in common. Students must still turn in assignments, participate in class, understand the content, and finish group projects. Teachers still need to create lesson plans, improve the quality of their teaching, respond to students' queries in class, encourage learning, and grade assignments.